2004
DOI: 10.1002/pds.945
|View full text |Cite
|
Sign up to set email alerts
|

Use of herbal drugs in pregnancy: a survey among 400 Norwegian women

Abstract: The widespread use of herbal drugs during pregnancy indicates an increased need for documentation about the safety of herbal drugs in pregnancy. To meet the needs of pregnant women, it is necessary for health care personnel to have knowledge about herbal drugs during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
155
2
15

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(196 citation statements)
references
References 24 publications
24
155
2
15
Order By: Relevance
“…The pattern of usage demonstrated by the women in this study where most women used herbal remedies throughout the period of pregnancy supported the finding of Nordeng and Havnen [1] which indicated an increasing pattern throughout the trimesters. This can be explained by the fact that most pregnant women were using it to protect their baby.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The pattern of usage demonstrated by the women in this study where most women used herbal remedies throughout the period of pregnancy supported the finding of Nordeng and Havnen [1] which indicated an increasing pattern throughout the trimesters. This can be explained by the fact that most pregnant women were using it to protect their baby.…”
Section: Discussionsupporting
confidence: 74%
“…Findings of this study also revealed that majority of the respondents have used herbal remedy to manage one or more illnesses related to pregnancy and this confirmed the work of Westfall [33] who reported that women utilize many coping strategies, including self-treatment with herbal medicine and other alternative therapies during pregnancy. Nordeng & Havnen [1] and Maats [34] also reported in their work that herbal medicines may be used during pregnancy to treat pregnancy symptoms like nausea and vomiting. They may also be used to prepare for labor or for other unrelated health issues such as colds and respiratory illnesses or skin problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em relação aos chás, Nordeng & Havnen 22 constataram que 39% daqueles usados pelas gestantes (n = 400) foram considerados como potencialmente prejudiciais. Para essa categoria apenas o intervalo interpartal curto (≤ 2 anos) mostrou associação, porém sem significância estatística, sugerindo que as mulheres que não adotam planejamento familiar tendem a utilizar mais produtos fitoterápicos do que as demais.…”
Section: Análise Dos Dadosunclassified
“…Although Chinese medicine was considered to have less toxicity and fewer side effects than traditional medicine, increasing evidence has shown this to be untrue (1)(2)(3). Given that many pregnant women use Chinese herbs for pregnancy-related sickness (4,5), the potential developmental toxicity of these herbs needs to be studied. In the present study, we investigated the safety and possible embryonic toxicity of four common herbs: Rhizoma Atractylodes macrocephala, Radix Isatidis, Coptis chinensis and Flos Genkwa.…”
Section: Introductionmentioning
confidence: 99%